2013
DOI: 10.1210/jc.2012-2028
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Dysfunction During Pregnancy and Thyroid Function of Her Child in Adolescence

Abstract: Maternal thyroid dysfunction and TPO-Ab positivity during pregnancy seem to modify thyroid function parameters of offspring even in adolescence. Whether this increases the thyroid disease risk of the children is still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
2
23
1
Order By: Relevance
“…The mean gestational age was 6.5 Ϯ 1.2 weeks for pregnant women. In pregnant women, the mean FT 4 level was higher (16.50 Ϯ 3.02 vs. 15.71 Ϯ 2.02 pmol/L, P Ͻ .001), and the median TSH level was lower (1.79 vs. 2.06 mIU/L, P Ͻ .001). The median SF level and mean TBI level of pregnant women were higher than those of nonpregnant women (64.76 vs. 51.27 g/L, P Ͻ .001 and 7.92 Ϯ 3.22 vs. 6.35 Ϯ 3.43 mg/kg, P Ͻ .001, respectively), and the median sTfR level was lower in pregnant women (2.67 vs. 3.11 mg/L, P Ͻ .001).…”
Section: Ethics Committee Approvalmentioning
confidence: 96%
See 2 more Smart Citations
“…The mean gestational age was 6.5 Ϯ 1.2 weeks for pregnant women. In pregnant women, the mean FT 4 level was higher (16.50 Ϯ 3.02 vs. 15.71 Ϯ 2.02 pmol/L, P Ͻ .001), and the median TSH level was lower (1.79 vs. 2.06 mIU/L, P Ͻ .001). The median SF level and mean TBI level of pregnant women were higher than those of nonpregnant women (64.76 vs. 51.27 g/L, P Ͻ .001 and 7.92 Ϯ 3.22 vs. 6.35 Ϯ 3.43 mg/kg, P Ͻ .001, respectively), and the median sTfR level was lower in pregnant women (2.67 vs. 3.11 mg/L, P Ͻ .001).…”
Section: Ethics Committee Approvalmentioning
confidence: 96%
“…Hypothyroxinemia during early pregnancy have become a focus in the field of maternal thyroid disorders, because of its probable detrimental effects on neuropsychological development of the offspring (8,10,11), while some other studies showed the inconsistent results (12)(13)(14)(15). However, the causes of hypothyroxinemia have not been clarified yet.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal TPO-Ab positivity during pregnancy has also been linked to abnormal thyroid function parameters in the offspring, even in adolescence [21]. As the presence of TAI also suggests the potential for decreased thyroid functional reserve during pregnancy, ensuring proper maternal iodine nutrition in these women is especially important.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term ATD therapy limited to the 1 st trimester resulted in normal foetal US performance observed in the 18 th -23 rd and the 30 th -33 rd WG. In view of the reports on the possible influence of maternal thyroid dysfunction during pregnancy on the pituitary-thyroid axis function in offspring [47], we compared the distribution of TSH levels obtained in dried-spot tests in children delivered by mothers with gestational hyperthyroidism and in the controls. No significant differences were noted between the two groups.…”
Section: Discussionmentioning
confidence: 99%